2020
DOI: 10.1080/13504851.2020.1830933
|View full text |Cite
|
Sign up to set email alerts
|

Stadium attendance demand during the COVID-19 crisis: early empirical evidence from Belarus

Abstract: In this note, we consider early evidence regarding behavioural responses to an emerging public health emergency. We explore patterns in stadium attendance demand by exploiting match-level data from the Belarusian Premier League (BPL), a football competition that kept playing unrestricted in front of spectators throughout the global COVID-19 pandemic, unlike all other European professional sports leagues. We observe that stadium attendance demand in Belarus declined significantly in the initial period of maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…Being aware of a limitation that the two samples differ to an extent (the Iranian respondents were younger and more frequently athletes and/or students), this study showed that most respondents will attend sporting events in their home countries within few weeks after all restrictions on movement and sporting event attendance will be lifted. This is in line with the study of spectators in Belarus Premier League during the COVID-19 crisis (Reade, Schreyer, & Singleton, 2020) and provides a breath of optimism for the event and sports tourism markets, which was considered to be one of the hardest hit tourism subsectors (Gössling, et al, 2020). Still, this does not mean that organisations' existing business models will stay the same; many will have to adapt and innovate focusing on new strategies to generate revenue such as ticketing strategies, digitalisation strategies, and media involvement (PwC's Sports Survey, 2020;.…”
Section: Discussionsupporting
confidence: 89%
“…Being aware of a limitation that the two samples differ to an extent (the Iranian respondents were younger and more frequently athletes and/or students), this study showed that most respondents will attend sporting events in their home countries within few weeks after all restrictions on movement and sporting event attendance will be lifted. This is in line with the study of spectators in Belarus Premier League during the COVID-19 crisis (Reade, Schreyer, & Singleton, 2020) and provides a breath of optimism for the event and sports tourism markets, which was considered to be one of the hardest hit tourism subsectors (Gössling, et al, 2020). Still, this does not mean that organisations' existing business models will stay the same; many will have to adapt and innovate focusing on new strategies to generate revenue such as ticketing strategies, digitalisation strategies, and media involvement (PwC's Sports Survey, 2020;.…”
Section: Discussionsupporting
confidence: 89%
“…Some leagues, primarily smaller European leagues such as the Danish Superliga, the Swiss Super League, and the Russian Premier League, eventually returned with some fans in attendance (e.g., Cueva, 2020). Only a few football leagues worldwide, most prominently the Belarussian Premier League (Reade et al, 2020a), kept playing throughout this first wave.…”
Section: Closed Doors Football After Covid-19 Home Advantage and Refmentioning
confidence: 99%
“…Furthermore, there is the commonly known circumstance that supporters are considered as the "12th man" who influence the outcome of the game in favor of their team (Edensor 2015 ), making ghost games especially intriguing for socio-economic and psychological analysis. Indeed, analyses of football matches played behind closed doors in the pre-COVID-19 era evidenced the impact of the fans on referee decisions (Pettersson-Lidbom and Priks 2010 ; Reade et al 2020a , b ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%